Arthroscopic outcomes in TMJ internal derangement and surgical progression in a single centre in New Zealand - Jamie Wayne Lockyer; Christopher GT Lim (Elsevier, 2021)
This study aims to examine outcomes for temporomandibular joint (TMJ) arthroscopy in different Wilkes stages of internal derangement (ID) and factors relevant in relapse in those requiring further surgical management. A review was undertaken of patients who underwent TMJ arthroscopy from June 2017 until August 2019 at St George's Medical Centre, Christchurch, New Zealand. Those with a primary diagnosis of ID with adequate follow up were reviewed. Gender, pre-and post-operative visual analogue scale (VAS) pain scores and maximum incisal opening (MIO) according to Wilkes stages were statistically analysed. Parameters of those who underwent further surgery were assessed. Ninety-nine patients were reviewed with follow up time between 3 and 27 months. No difference in pre- and post-operative VAS pain scores occurred between Wilkes stages (p = 0.9527). Wilkes II patients had the lowest re-operation rates (6.7%). Twenty-one percent of patients underwent further surgery with either re-arthroscopy, arthrotomy or total joint replacement. Gender did not influence the risk of further surgery (p = 0.3451). Four Wilkes IV and 5 Wilkes V patients underwent TJR, with none from Wilkes II or III. This study shows TMJ arthroscopy should be considered a first line intervention in treating symptomatic ID regardless of initial Wilkes stage. A significant improvement in pain and functional levels occurred across all stages. No specific factors were identified for those undergoing further surgery. However, a trend towards open surgery and total joint replacement was seen in Wilkes IV and V patients.